2014
DOI: 10.1007/s11239-014-1101-6
|View full text |Cite
|
Sign up to set email alerts
|

d-Dimer elevation and adverse outcomes

Abstract: d-Dimer is a biomarker of fibrin formation and degradation. While a d-dimer within normal limits is used to rule out the diagnosis of deep venous thrombosis and pulmonary embolism among patients with a low clinical probability of venous thromboembolism (VTE), the prognostic association of an elevated d-dimer with adverse outcomes has received far less emphasis. An elevated d-dimer is independently associated with an increased risk for incident VTE, recurrent VTE, and mortality. An elevated d-dimer is an indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 50 publications
4
73
0
4
Order By: Relevance
“…Clinically, extremely elevated levels of D-dimer are a hallmark of disseminated intravascular coagulation, while D-dimer levels in the normal range are used to exclude a diagnosis of deep venous thrombosis and pulmonary embolism. 1 In healthy people, higher D-dimer predicts future risk of cardiovascular disease (CVD) events, 2, 3 particularly venous thrombosis, 4, 5 stroke, 6, 7 and all-cause mortality 8, 9 independently of conventional CVD risk factors. More modest associations have generally been observed for incident coronary heart disease (CHD).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, extremely elevated levels of D-dimer are a hallmark of disseminated intravascular coagulation, while D-dimer levels in the normal range are used to exclude a diagnosis of deep venous thrombosis and pulmonary embolism. 1 In healthy people, higher D-dimer predicts future risk of cardiovascular disease (CVD) events, 2, 3 particularly venous thrombosis, 4, 5 stroke, 6, 7 and all-cause mortality 8, 9 independently of conventional CVD risk factors. More modest associations have generally been observed for incident coronary heart disease (CHD).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an association between elevated D-dimer and increased mortality in 30 days and 3 months after PE. Similarly, it has been associated with higher mortality in cancer patients [22]. PESI was determined to be an independent prognostic factor in the 90-day follow-up period but not at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in accordance with previous studies that show NTproBNP has 100% sensitivity in detecting cardiac involvement in AL amyloidosis [13] and D-dimer is a potential biomarker in cardiovascular diseases. D-dimer is a product of fibrinolysis [14][15][16][17], and plasma levels of D-dimer may indicate disease severity and predict outcome in patients with heart failure [5,14]. In addition, D-dimer has been reported as a sensitive marker for early detection of acute myocardial infarction [18].…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer levels are widely used clinically to detect patients with suspected disseminated intravascular coagulation, thromboembolic events, and myocardial infarction [15]. Furthermore, D-dimer is an independent correlate of increased mortality and venous thrombosis across a variety of disease states [14,20]. D-dimer positively correlates with biomarkers of inflammation.…”
Section: D-dimer and Venous Thrombosis/inflammatorymentioning
confidence: 99%